Epistemologi Eksistensialisme Muhammad Iqbal dan Relevansinya bagi Ilmu Pendidikan (Islam) - Salimah, Binti (MAN 1 Kota Kediri, 2023)
The epistemology of Muhammad Iqbal's existentialism is a philosophical approach that examines the sources of knowledge and the worldview presented by the great Islamic thinker, Muhammad iqbal. Merging the idea of existentialism with the doctrine of Islam to develop a deeper understanding of the truth of man, knowledge, and existence. In an era of globalization and complex challenges faced by Muslim societies, the epistemology of Muhammad Iqbal's existentialism carries an important message that Islamic education must bridge spiritual understanding with rational understanding. It will help create a spiritually strong generation, have a strong Islamic identity, and be able to contribute positively to the development of society and the world in general. In the world of education, it is hoped that there should be no man who should have a uniform mind, because man is not a thing, but a self who acquires consciousness, freedom and uniqueness. So education should be open and centered on the interests and wishes of the students.